1995
DOI: 10.1212/wnl.45.5.903
|View full text |Cite
|
Sign up to set email alerts
|

Lack of association of apolipoprotein E allele ϵ4 with late‐onset Alzheimer's disease among Finnish centenarians

Abstract: No association between Alzheimer's disease (AD) and apolipoprotein E type epsilon 4 (ApoE epsilon 4) phenotype was found among centenarians in Finland (N = 179). The data are based on ascertainment of all centenarians in Finland in 1991. All examinations were conducted during 1991. The diagnoses of dementia and AD were based on clinical grounds, conforming to DSM-III-R and NINCDS-ADRDA criteria. The percentage of ApoE epsilon 4 alleles among the centenarians was 8.7% (31 of 358 alleles). This is significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
52
4

Year Published

1995
1995
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(62 citation statements)
references
References 4 publications
6
52
4
Order By: Relevance
“…Some studies of participants aged 85+ found the presence of an e4 allele to be related to prevalent AD [36][37][38] but this was not the case in a study of Finnish centenarians [39]. Furthermore, it is not known if agents that potentially confer protection in younger subjects such as folate, non-steroidal anti-inflammatory drugs, statins, antioxidants, estrogen therapy, and physical and cognitive activities are operative for individuals in extreme old age.…”
Section: Risk and Protective Factors For Dementia And Ad In The Oldesmentioning
confidence: 95%
“…Some studies of participants aged 85+ found the presence of an e4 allele to be related to prevalent AD [36][37][38] but this was not the case in a study of Finnish centenarians [39]. Furthermore, it is not known if agents that potentially confer protection in younger subjects such as folate, non-steroidal anti-inflammatory drugs, statins, antioxidants, estrogen therapy, and physical and cognitive activities are operative for individuals in extreme old age.…”
Section: Risk and Protective Factors For Dementia And Ad In The Oldesmentioning
confidence: 95%
“…While there was a significant negative association between the ε4 allele and cognitive function among 103 Korean centenarians (Choi et al 2003), this finding was not observed in 179 Finnish (Sobel et al 1995) and 33 Japanese centenarians (Asada et al 1996).…”
mentioning
confidence: 70%
“…In previous studies on centenarians, effects of the APOE ε4 allele on cognitive function have been inconsistent (Asada et al 1996;Choi et al 2003;Sobel et al 1995). These inconsistent findings could be attributed to common characteristics of centenarian studies: small sample size, skewed distribution of APOE genotype, and lesser attention of researchers with regard to the effect of life course environment on cognitive function in centenarian study (Hofer and Alwin 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The extent of the ~4 effect is diminished in the very elderly (Rebeck et al, 1994;Sobel et al, 1995) and many can reach old age without cognitive impairment despite the inheritance of one or two APOE ~4 alleles (Hymanet al, 1996). Use of APOE genotype in predictive test situations, however, requires absolute risk information that can be obtained only from prospective cohort studies, a number of which are under way (Brayne et al, 1996;Feskens et al, 1994;Henderson et al, 1995;Hyman et al, 1996;Kuusisto et al, 1994;Myers et al, 1996;Petersen et al, 1995).…”
Section: Apoe Genotype and Its Interaction With Other Genesmentioning
confidence: 99%